Crystallographic Transformation: Room‐Temperature AFM Electric‐Field‐Induced Topotactic Transformation between Perovskite and Brownmillerite SrFeOx with Sub‐Micrometer Spatial Resolution (Adv. Funct. Mater. 48/2019). (26th November 2019) - Ferreiro‐Vila, Elías; Blanco‐Canosa, Santiago; Lucas del Pozo, Irene; Vasili, Hari Babu; Magén, César; Ibarra, Alfonso; Rubio‐Zuazo, Juan; Castro, Germán R.; Morellón, Luis; Rivadulla, Francisco
Abstract : Structural transformation between perovskite SrFeO3− δ and brownmillerite SrFeO2.5 can be induced by topotactic oxygen exchange at moderate temperatures under reducing conditions. In article number 1901984, Elías Ferreiro‐Vila, Francisco Rivadulla, and co‐workers show that the electric field produced by a voltage‐biased AFM tip can induce such transformation at room temperature. This allows non‐volatile control of the functional properties with sub‐micron spatial resolution.